2017
DOI: 10.12968/bjon.2017.26.sup20a.s4
|View full text |Cite
|
Sign up to set email alerts
|

Role of slough and biofilm in delaying healing in chronic wounds

Abstract: The management of biofilms with maintenance desloughing and antimicrobial therapy is fast becoming the accepted treatment strategy for chronic wounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Moreover, a number of studies of chronic wounds reported that the treatment rapidly eliminated slough over 4 weeks' treatment, 25,26,33 and a study on sloughy wounds reported that, as early as week 1, the reduction in the quantity of slough in the local haemoglobin group (67%) was greater than that in the historical control group (8%) 22 . Slough provides an ideal environment for the survival and growth of biofilms, which increases the risk of wound infection and a delay in wound healing 43,44 . Therefore, the management of slough should be addressed as an important element of wound care.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, a number of studies of chronic wounds reported that the treatment rapidly eliminated slough over 4 weeks' treatment, 25,26,33 and a study on sloughy wounds reported that, as early as week 1, the reduction in the quantity of slough in the local haemoglobin group (67%) was greater than that in the historical control group (8%) 22 . Slough provides an ideal environment for the survival and growth of biofilms, which increases the risk of wound infection and a delay in wound healing 43,44 . Therefore, the management of slough should be addressed as an important element of wound care.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the management of slough should be addressed as an important element of wound care. Traditional treatments utilise debridement and other desloughing techniques, but repeated debridement undoubtedly causes considerable pain to patients with increased medical costs 44 . Due to the outstanding benefits of local haemoglobin spray in reducing slough and pain relief, a number of researchers recommend haemoglobin spray as a first‐line debridement technique instead of traditional treatments 22 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Skin is the largest organ of the human body, with the main function to protect the inner tissues from invasion of microorganisms of endogenous (skin flora) and exogenous sources. However, in case of skin lesions or wounds, microbes that can evade the host’s first lines of defense can adhere to the underlying soft tissues, proliferate and start to produce exopolymeric substances to form a biofilm 1. Biofilm is defined as an aggregate community of microbial cells, embedded in a self-produced slime layer of polymeric substances and adherent to biotic or abiotic surfaces 2.…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al and Kennedy et al also found that most bacteria were localised in the eschar rather than at the wound surface. These studies demonstrated that eschar serves as a reservoir for microorganisms, biofilms, necrotic tissue, and inflammatory chemokines that are important factors that form a hostile local milieu hindering fibroblast and keratinocyte proliferation and migration . Eschar is difficult to remove, and its presence can lead to a delay in wound healing.…”
Section: Introductionmentioning
confidence: 99%